2012
DOI: 10.1107/s1600536812002061
|View full text |Cite
|
Sign up to set email alerts
|

Diaquabis[5-(pyrazin-2-yl)-3-(pyridin-4-yl)-1H-1,2,4-triazol-1-ido-κN1]zinc

Abstract: The title mononuclear complex, [Zn(C11H7N6)2(H2O)2], is composed of one ZnII ion, two deprotonated ppt ligands [Hppt = 5-(pyrazin-2-yl)-3-(pyridin-4-yl)-1H-1,2,4-triazole] and two coordinating water mol­ecules. The asymmetric unit consists of one half-mol­ecule that is completed by application of a centre of symmetry. The ZnII atom is six-coordinated in an octa­hedral environment, surrounded by two O atoms in the axial positions and four N atoms in the equatorial plane. Adjacent mononuclear units are further l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…In this contribution, we have investigated a pyridine and pyrazine-substituted triazole tecton, 3-(pyridin-4-yl)-5-(pyrazin-2-yl)-1H-1,2,4-triazole (HL), which is an angular pyridyl-pyrazinyl ligand that may show different conformations depending on the conditions used for constructing metalorganic frameworks. Coordination of pyridine and pyrazine substituted triazole to metal ions has only been the subject of limited study, and to our knowledge, only two examples with HL have been reported [19,20]. (1) and [CdL 2 ] n (2), respectively.…”
Section: Introductionmentioning
confidence: 96%
“…In this contribution, we have investigated a pyridine and pyrazine-substituted triazole tecton, 3-(pyridin-4-yl)-5-(pyrazin-2-yl)-1H-1,2,4-triazole (HL), which is an angular pyridyl-pyrazinyl ligand that may show different conformations depending on the conditions used for constructing metalorganic frameworks. Coordination of pyridine and pyrazine substituted triazole to metal ions has only been the subject of limited study, and to our knowledge, only two examples with HL have been reported [19,20]. (1) and [CdL 2 ] n (2), respectively.…”
Section: Introductionmentioning
confidence: 96%